Caracterização microestrutural de hidroxiapatita obtida por precipitação pelo método de via úmida para possível aplicação como um biomaterial - NASCIMENTO, Damares da Cruz Barbosa (2022)
The search for materials with bioactive, osteoconductive and biocompatible characteristics has been widely investigated nowadays, due to the problems (accidents and bone failures) faced by society. From this arises Hydroxyapatite (HA), an inorganic bioceramic that presents particularities and similarities to the mineral apatite, found mainly in human bones and teeth. Its characteristics, with biocompatibility, cell adhesion, bioactivity and degradation are fundamental for possible applications as a biomaterial, in the performance of bone regeneration. As it is a calcium phosphate (Ca10(PO4)6(OH)2), many researches investigate routes that make it possible to obtain hydroxyapatite in its synthetic form, trying to get closer to the natural mineral. Thus, this work aims to synthesize and characterize hydroxyapatite using a precipitation technique by the wet method, using acid/base reagents of 0.5, 1.0, and 1.5 molar phosphoric acid (H2PO4) and ammonium hydroxide (NH4OH), in addition to calcium hydroxide (Ca(OH)2). In addition, vary the sintering parameters of 900 °C and 1000 °C for a period of 2 hours at a heating rate of 10 °C/min. In order to analyze the chemical elements and the microstructure of the material obtained, the techniques of Fourier Transform Infrared Spectroscopy (FTIR), X-ray Diffraction (XRD), Rietveld Refinement, Scanning electron Microscopy (SEM) were performed. and Energy Dispersive spectroscopy (EDS). The FTIR results showed vibration bands of carbonates (CO3 2-) and phosphates (PO4 3-), characteristic for the material. As for the XRD, it showed hydroxyapatite and calcium oxide peaks, with crystallite sizes between 50 - 63 nm and crystallinity above 80%. Regarding the Rietveld refinement, percentages above 90% and GOF from 1 to 1.35 were obtained. In addition to these characterizations, SEM analyzes indicated irregular morphologies with different shapes and forms. Furthermore, by EDS analysis, the presence of calcium, phosphorus and oxygen was observed and also, through this result, the molar ratio of Ca/P between 1.50 and 1.72 was determined. The characterizations performed indicated the presence of type B carbonated hydroxyapatite, suggesting a manometric format, with good crystallinity and dense. Furthermore, it is suggested that the hydroxyapatite obtained in this study has great potential to be applied as a biomaterial.